Enhancing Understanding of the Visual Cycle by Applying CRISPR/Cas9 Gene Editing in Zebrafish - Ward, Rebecca; Sundaramurthi, Husvinee; Di Giacomo, Valeria; Kennedy, Breandán N. (Frontiers in Cell and Developmental Biology, 2018)
During the vertebrate visual cycle, all-trans-retinal is exported from photoreceptors to the adjacent RPE or Müller glia wherein 11-cis-retinal is regenerated. The 11-cis chromophore is returned to photoreceptors, forming light-sensitive visual pigments with opsin GPCRs. Dysfunction of this process perturbs phototransduction because functional visual pigment cannot be generated. Mutations in visual cycle genes can result in monogenic inherited forms of blindness. Though key enzymatic processes are well characterised, questions remain as to the physiological role of visual cycle proteins in different retinal cell types, functional domains of these proteins in retinoid biochemistry and in vivo pathogenesis of disease mutations. Significant progress is needed to develop effective and accessible treatments for inherited blindness arising from mutations in visual cycle genes. Here, we review opportunities to apply gene editing technology to two crucial visual cycle components, RPE65 and CRALBP. Expressed exclusively in the human RPE, RPE65 enzymatically converts retinyl esters into 11-cis retinal. CRALBP is an 11-cis-retinal binding protein expressed in human RPE and Muller glia. Loss-of-function mutations in either protein results in autosomal recessive forms of blindness. Modelling these human conditions using RPE65 or CRALBP murine knockout models have enhanced our understanding of their biochemical function, associated disease pathogenesis and development of therapeutics. However, rod-dominated murine retinae provide a challenge to assess cone function. The cone-rich zebrafish model is amenable to cost-effective maintenance of a variety of strains. Interestingly, gene duplication in zebrafish resulted in three Rpe65 and two Cralbp isoforms with differential temporal and spatial expression patterns. Functional investigations of zebrafish Rpe65 and Cralbp were restricted to gene knockdown with morpholino oligonucleotides. However, transient silencing, off-target effects and discrepancies between knockdown and knockout models, highlight a need for more comprehensive alternatives for functional genomics. CRISPR/Cas9 in zebrafish has emerged as a formidable technology enabling targeted gene knockout, knock-in, activation or silencing to single base-pair resolution. Effective, targeted gene editing by CRISPR/Cas9 in zebrafish enables unprecedented opportunities to create genetic research models. This review will discuss existing knowledge gaps regarding RPE65 and CRALBP. We explore the benefits of CRISPR/Cas9 to establish innovative zebrafish models to enhance knowledge of the visual cycle.